Provocation in women's filmmaking : authorship and art cinema - Loreck, Janice, 1986-; Edinburgh University Press (Edinburgh : Edinburgh University Press, 2023)
A new critical perspective on the female auteur that considers her place in the avant-garde tradition of provocation. Includes close critical analysis of eight contemporary women filmmakers and their provocative works. Provides an exploration and account of provocation as an artistic strategy in cinema. Offers a feminist interrogation of the gendering of provocation, and the provocateur, in the discourses of film criticism as a masculine mode. Critics regularly use the term provocateur to describe controversial film directors. Although most individuals who attract this term are men, there is a long and largely unexamined history of female auteurs who shock and unsettle their viewers. Provocation in Women's Filmmaking: Authorship and Art Cinema investigates how women directors participate in the tradition of provocative art cinema. Focusing on the post-millennium films of auteurs such as Lisa Aschan, Catherine Breillat, Jennifer Kent, Isabella Eklöf, Lucile Hadžihalilović, Claire Denis, Anna Biller and Athina Rachel Tsangari, this book considers the aesthetics and strategies of women's provocative filmmaking in contemporary cinema. Challenging the gendering of provocation as a hyper-masculine mode of authorship, the book uncovers an enticing and complex array of divisive works by women.
Sexuality and obscenity : from Catherine Breillat to Lisa Aschan -- On not looking away : rape in the films of Jennifer Kent and Isabella Eklöf -- The provocations of the pretty : the films of Lucile Hadžihalilović -- Pursuing transgression : Claire Denis's taboo intimacies -- Posing as an innocent : irony, sincerity and Anna Biller -- Vaguely disturbing : humour in the films of Athina Rachel Tsangari.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (ProQuest Ebook Central, viewed January 4, 2024).
JSTOR
Keywords: Women motion picture producers and directors; Motion pictures -- Production and direction -- Philosophy; Motion pictures -- Production and direction -- Philosophy and aesthetics; Feminism and motion pictures; Cinematography -- Philosophy and aesthetics -- History and criticism; Aversion -- Philosophy and aesthetics -- In motion pictures; Distress (Psychology) -- Philosophy and aesthetics -- In motion pictures; Discomfort (Psychology) -- Philosophy and aesthetics -- In motion pictures; Ethical problems -- In motion pictures; Sexual ethics -- In motion pictures -- History and criticism; Transgression (Ethics) -- In motion pictures -- History and criticism; Auteur theory (Motion pictures) -- Women; Productrices et réalisatrices de cinéma.; Cinéma -- Production et réalisation -- Philosophie; Féminisme et cinéma.; Cinéma -- Production et réalisation -- Philosophie et esthétique.; Aversion -- Philosophie et esthétique -- Au cinéma.; Détresse -- Philosophie et esthétique -- Au cinéma.; Malaise (Psychologie) -- Philosophie et esthétique -- Au cinéma.; Problèmes moraux -- Au cinéma.; Morale sexuelle -- Au cinéma -- Histoire et critique; Transgression -- Au cinéma -- Histoire et critique; Politique des auteurs (Cinéma) -- Femmes; filmmakers; PERFORMING ARTS / Film & Video / Direction & Production; Feminism and motion pictures; Women motion picture producers and directors; Film criticism; Critiques cinématographiques.